Modulation of multidrug-resistant clone success in Escherichia coli populations: a longitudinal, multi-country, genomic and antibiotic usage cohort study - Pöntinen, Anna K. (Elsevier, 2025)
Background: The effect of antibiotic usage on the success of multidrug-resistant (MDR) clones in a population remains unclear. With this genomics-based molecular epidemiology study, we aimed to investigate the contribution of antibiotic use to Escherichia coli clone success, relative to intra-strain competition for colonisation and infection.
Methods: We sequenced all the available E coli bloodstream infection isolates provided by the British Society for Antimicrobial Chemotherapy (BSAC) from 2012 to 2017 (n=718) and combined these with published data from the UK (2001-11; n=1090) and Norway (2002-17; n=3254). Defined daily dose (DDD) data from the European Centre for Disease Prevention and Control (retrieved on Sept 21, 2021) for major antibiotic classes (β-lactam, tetracycline, macrolide, sulfonamide, quinolone, and non-penicillin β-lactam) were used together with sequence typing, resistance profiling, regression analysis, and non-neutral Wright-Fisher simulation-based modelling to enable systematic comparison of resistance levels, clone success, and antibiotic usage between the UK and Norway.
Findings: Sequence type (ST)73, ST131, ST95, and ST69 accounted for 892 (49·3%) of 1808 isolates in the BSAC collection. In the UK, the proportion of ST69 increased between 2001-10 and 2011-17 (p=0·0004), whereas the proportions of ST73 and ST95 did not vary between periods. ST131 expanded quickly after its emergence in 2003 and its prevalence remained consistent throughout the study period (apart from a brief decrease in 2009-10). The extended-spectrum β-lactamase (ESBL)-carrying, globally disseminated MDR clone ST131-C2 showed overall greater success in the UK (154 [56·8%] of 271 isolates in 2003-17) compared with Norway (51 [18·3%] of 278 isolates in 2002-17; p<0·0001). DDD data indicated higher total use of antimicrobials in the UK, driven mainly by the class of non-penicillin β-lactams, which were used between 2·7-times and 5·1-times more in the UK per annum (ratio mean 3·7 [SD 0·8]). This difference was associated with the higher success of the MDR clone ST131-C2 (pseudo-R2 69·1%). A non-neutral Wright-Fisher model replicated the observed expansion of non-MDR and MDR sequence types under higher DDD regimes.
Interpretation: Our study indicates that resistance profiles of contemporaneously successful clones can vary substantially, warranting caution in the interpretation of correlations between aggregate measures of resistance and antibiotic usage. Our study further suggests that in countries with low-to-moderate use of antibiotics, such as the UK and Norway, the extent of non-penicillin β-lactam use modulates rather than determines the success of widely disseminated MDR ESBL-carrying E coli clones. Detailed understanding of underlying causal drivers of success is important for improved control of resistant pathogens.